Interception of values as a result of the business model restructuring - case study = Przechwytywanie wartości w wyniku restrukturalizacji modelu biznesowego - studium przypadku - Nogalski, Bogdan; Niewiadomski, Przemysław (Zielona Góra: Faculty of Economics and Management Press)
The main objective of this paper is to present a case of value interception as a result of restructuring the business model of a manufacturing company that operates in the agricultural machinery sector. A company that focuses on core activities in the value chain and commissions the manufacturing of most components to specialised suppliers - as a result of restructuring - becomes an integrator that controls all parts of the supply chain; from obtaining a raw material, through its own production of a possibly large number of components, to the distribution of a finished composite product.
Keywords: modele biznesu; elastyczność implementacyjna; strategia; sektor maszyn rolniczych; business models; implementation flexibility; strategy; agricultural machinery sector